Effectiveness of Sodium Polyacrylate (Superabsorbent Polymer) as a Growing Medium of Hydroponically Grown Ocimum Basilicum (Basil) - Macabale, Xedny Rhiane S.; Quimada, Leonah Reggie L.; Torrentira, Angel Janine B.; Vergara, Chiara Arabelle J.; Zapanta, Ariell Kathleen A.; Catarina, Nikko C.; Olandria, Maria Lordan L. (International Journal on Integrated Education, 2023)
Sodium polyacrylate is a synthetic polymer that belongs to the class of superabsorbent polymers (SAPs). It is commonly referred to as a water-absorbing polymer due to its remarkable ability to absorb and retain large amounts of water. One of its primary uses is in disposable diapers, feminine hygiene products, and adult incontinence products, where it serves as a highly effective absorbent core that can retain large amounts of liquid while preventing leakage. In the present experimental quantitative study, the researchers aim to determine the feasibility of utilizing Sodium Polyacrylate as a growing medium for Basil (Ocimum basilicum) in a Hydroponics Kratky Method System. The instrument used in data gathering was a Hydroponics Kratky setup. In the Kratky method, plants were grown in Styrofoam containers filled with a nutrient solution that is initially at a level high enough to cover the roots. As the plants grow and take up water and nutrients, the nutrient solution level gradually decreases, leaving the roots partially submerged in the remaining solution. The method relied on the natural process of plant growth to create a balanced system, without the need for pumps or aeration devices. Findings show that Sodium Polyacrylate exhibits excellent water retention properties, strong enough to extend Ocimum basilicum’s lifespan compared to any other Hydroponics Growing Medium. Sodium polyacrylate can absorb and retain water at a rate of 100 to 1,000 times its weight. The results of this investigation indicate that Sodium Polyacrylate has immense potential in the innovation of Horticulture and the development of the agriculture industry, specifically in the field of Hydroponic.